Work Motivation and Employee Performance at the Department of Manpower Office in Makassar City - Firda Amanda Wulandari; Herlina Sakawati; Haedar Akib (Jurnal Aktor, 2023)
This research aims to determine the quality of service for claim participants of the social security organizers of employment in the BPJS Ketenagakerjaan office in Makassar City. This research uses a qualitative approach and employs descriptive research design. Data collection is conducted through field observations, interviews, and documentation. The data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions. The results of this research indicate that the service for claim participants of the social security organizers of employment can be seen from five indicators of service quality: 1) Tangibles (Physical Evidence) are good, 2) Reliability is not yet well-implemented, 3) Responsiveness is good, 4) Assurance is well-implemented, and 5) Empathy is well-implemented. Based on the research results, four out of five indicators of service quality have been well-implemented and meet the standards of service quality.